An optimal schedule for printing and binding - Chin, Francis; Wong, Michael (International journal of computer mathematics, 1984)
An optimal solution is presented for the scheduling of printing and binding of a book order. The algorithm is simpler and faster than previously known methods. If the book is divided into n parts and the typesetting time for each part is different, the algorithm takes steps. The algorithm operates in linear time if all the typesetting times are identical. The problem can be generalized easily to other problems and its optimal solution can be applied to other two-stage production processes with overheads for interruptions.